2012
DOI: 10.1021/bc300184m
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Macrocyclization of Peptides Fused to Antibody Fc Fragments

Abstract: To extend the plasma half-life of a bicyclic peptide antagonist, we chose to link it to the Fc fragment of the long-lived serum protein IgG1. Instead of chemically conjugating the entire bicyclic peptide, we recombinantly expressed its peptide moiety as a fusion protein to an Fc fragment and subsequently cyclized the peptide by chemically reacting its three cysteine residues with tris-(bromomethyl)benzene. This reaction was efficient and selective, yielding completely modified peptide fusion protein and no sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
(50 reference statements)
0
21
0
Order By: Relevance
“…[22] Thioether crosslinks are generally more difficult to introduce into proteins than into short peptides, but incorporation can be achieved by enzymatic modification or chemical strategies such as alkylation of cysteine residues by crosslinking agents. [23][24][25] However, for small (< 80 aa) proteins, producProtein-based pharmaceuticals typically display high selectivity and low toxicity, but are also characterized by low oral availability, mainly because of enzymatic degradation in the gastrointestinal tract and poor permeability across the intestinal wall. One way to increase the proteolytic stability of peptides and proteins is by intramolecular crosslinking, such as the introduction of disulfide bridges.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Thioether crosslinks are generally more difficult to introduce into proteins than into short peptides, but incorporation can be achieved by enzymatic modification or chemical strategies such as alkylation of cysteine residues by crosslinking agents. [23][24][25] However, for small (< 80 aa) proteins, producProtein-based pharmaceuticals typically display high selectivity and low toxicity, but are also characterized by low oral availability, mainly because of enzymatic degradation in the gastrointestinal tract and poor permeability across the intestinal wall. One way to increase the proteolytic stability of peptides and proteins is by intramolecular crosslinking, such as the introduction of disulfide bridges.…”
Section: Introductionmentioning
confidence: 99%
“…As a safety catch, cysteines in the Fc hinge region were replaced by serines. Additionally, the hinge region was shortened to a length of 12 amino acids, as shown in another study with cysteine‐rich peptides displayed on Fc . Gel filtration analysis confirmed that this Fc construct lacking intermolecular disulfides still formed homodimers, mainly because of hydrophobic interactions of the CH3 domains .…”
Section: Discussionmentioning
confidence: 70%
“…Notably, the use of multi-thiol-reactive linkers has a remarkably long tradition, as an application for this purpose of the aromatic derivative, 1,3,5-tris(bromomethyl)benzene, was initially reported by Kemp & McNamara in 1985 (Kemp and McNamara, 1985) and use of its bis-reactive homologs, 1,2-bis(bromomethyl)benzene, and 1,3-bis(bromomethyl)benzene was described only few years later (Szewczuk et al, 1992). This methodology was also successfully applied in peptide drug development (Timmerman et al, 2007), including phage display (Angelini et al, 2012a; Baeriswyl et al, 2012; Baeriswyl et al, 2013; Baeriswyl and Heinis, 2013a; Baeriswyl and Heinis, 2013b; Bellotto et al, 2014; Chen et al, 2012; Chen et al, 2013; Chen et al, 2014b; Chen et al, 2014a; Heinis et al, 2009; Rentero-Rebollo et al, 2014; Timmerman et al, 2007) as well as peptide-albumin (Angelini et al, 2012c; Pollaro et al, 2014) and peptide-antibody drug conjugates (ADCs) (Angelini et al, 2012b). …”
Section: Introductionmentioning
confidence: 99%